Ligandin in the steroidogenic tissues of the rat : characterisation, distribution and development - Eidne, Karin Ann (Division of Chemical Pathology, 2018)
One of the main problems in the field of multifunctional proteins such as ligandin is the possibility that multiple forms and isoproteins may exist. Two forms of liver ligandin [ GSH (reduced glutathione) S-transferase B] have been described, a heterodimeric form consisting of equal amounts of Ya (22000 daltons) and Yc (25000 daltons) subunits, and a homodimeric form containing only Ya. Because rat testis ligandin, prepared by the standard technique of anion-exchange and molecular exclusion chromatography, contains more Yc subunit than Ya, it has been claimed that testis and liver ligandin are different entities (Bhargava, Ohmi, Listowsky and Arias (1980) J. Biol. Chem. 255, 724-727). This thesis investigated the nature and character of ligandin in the steroid-producing tissues of the rat. A comparative study was undertaken to establish whether testis ligandin differed from liver ligandin. Different methods of purification were used to investigate testis ligandin and its relationship to other GSH S-transferases in steroidogenic tissues. Testis ligandin purified by immunoaffinity chromatography using anti-liver YaYa ligandin antiserum yielded a product identical with liver preparations (Yc=Ya). This suggests that the differences previously described may be due to contamination of testis ligandin by a closely related species. Testis ligandin prepared by the standard technique was similar to that previously reported, containing more Yc than Ya. Cross-linking studies of standard testis ligandin preparations with dimethylsuberimidate showed more than one band in the 50000 dalton region, further strengthening the view that these testis ligandin preparations may be contaminated. Since this contaminant was likely to be another GSH S-transferase, sodium dodecyl sulphate/ polyacrylamide-gel-electrophoretic analysis was performed on testis GSH S-transferases separated by CM-cellulose chromatography. GSH S-transferase AA which was present in large amounts, was shown to migrate in the same region as Yc subunit. CM-cellulose chromatography of a 'pure' standard testis ligandin preparation revealed significant amounts of GSH S-transferase AA migrating as Yc subunit, in addition to ligandin consisting of equal amounts of Ya and Yc subunits, indicating that testis ligandin is identical with liver ligandin and that previously described differences are due to a contaminant identified as GSH S-transferase AA. Studies on ligandin in other steroid-synthesising tissues showed that ovary and adrenal ligandin prepared by standard techniques also contained more Yc than Ya. Separation of ovary GSH S-transferases on CM-cellulose showed that GSH S-transferase B, the peak reacting with anti-liver YaYa ligandin antisera contained equal amounts of Ya and Y c subunits, suggesting a situation similar to that in the testis exists. Glutathione peroxidase II activity of testis and ovary GSH S-transferases was investigated. Fractions corresponding to GSH S-transferase AA, A and B exhibited activity with cumene hydroperoxide. The considerable glutathione peroxidase activity of GSH S-transferases in testis and ovary suggest a protective function for the cells of gonadal tissue against oxidative damage to essential intracellular components. Further attempts to clarify the function of ligandin in the steroid-synthesising tissues were made. The pattern of gonadal ligandin development during early life, puberty and pregnancy determined by radioimmunoassay was found to parallel serum steroid hormone concentrations. This correlation was not observed in liver or kidney. Ligandin was localised to specific cells of the steroid synthesising tissues using immunocytochemical techniques. These findings suggest that there may be a functional link between steroidogenic cells, or products of their activity and certain GSH S-transferases. Phenobarbital pre-treatment did not have any effect on developing testis, ovary or adrenal ligand in concentrations. Immunocytochemical localisation of ligandin in rat steroid-producing tissues using a peroxidase anti-peroxidase (PAP) technique with anti-liver YaYa ligandin antiserum as the first antibody, showed staining in the testis to be limited to the interstitial (Leydig) cells. Stromal cells of the ovary and the fascicular, glomerular and reticular zones of the adrenal cortex also contained immunoreactive material. PAP staining with anti-testis ligandin antisera (testis ligandin prepared using the standard technique) showed far greater intensity of staining in these tissues, presumably due to reaction with both ligand in and GSH S-transferase AA. This study has clarified the structural aspects of testis ligandin and demonstrated identity with liver ligandin. Ontogeny of ligandin in the steroidogenic tissues and localisation to specific regions in these tissues suggests a functional link between ligandin, GSH S-transferases, GSH peroxidases and activity of steroidogenic tissue.